Mobile satellite communications principles and trends - Richharia, M. (Madhavendra) (Chichester, West Sussex : John Wiley & Sons, 2011)
"Demand for Mobile Satellite Service (MSS) is on the increase, with a huge surge of interest in mobile communications in recent years and high-paced advancements in the supporting system architectures, devices and applications. This thoroughly revised and updated book provides a comprehensive guide to the MSS technologies and emerging trends. It takes a system level approach, giving in-depth treatment of technical and business related issues. The author, a leading professional in the area, draws on his extensive experience in industry and research, to provide the reader with a sound and info."--Provided by publisher.
Cover; Title Page; Copyright; Contents; Preface; About the Author; Acknowledgements; Chapter 1 Introduction; 1.1 Scope and Organization; 1.2 Evolution of Mobile Telecommunications; 1.2.1 Terrestrial Systems; 1.2.2 Satellite Systems; 1.3 Satellite System Architecture; 1.3.1 Radio Frequency Environment; 1.3.2 Orbit; 1.3.3 Tolerable Delay in Data Delivery; 1.3.4 Handover; 1.3.5 Mobility Management; 1.3.6 Physical Environment; 1.3.7 Satellite Access; 1.3.8 Spectrum Management; 1.3.9 Radio Link Reliability; 1.4 Business Plan; 1.5 Regulatory Considerations; 1.6 Operational Considerations. 1.7 Mobile Systems-A Comparison1.8 Example Applications; 1.9 Practical Limitations; 1.10 Related Satellite Systems; 1.10.1 M-VSAT Systems; 1.10.2 Satellite Navigation Systems; 1.10.3 Direct Broadcasts to Individuals and Mobiles; 1.11 Trends; 1.11.1 General; 1.11.2 Market; 1.11.3 System Architecture; 1.11.4 Spectrum; 1.11.5 Technology; Revision; References; Chapter 2 Satellite Constellations; 2.1 Introduction; 2.2 Satellite Orbits; 2.2.1 Orbital Mechanics Basics; 2.2.2 Satellite Coverage; 2.2.3 Space Environment; 2.2.4 Eclipse on Satellites; 2.2.5 The Sun's Interference; 2.2.6 Doppler Effect. 2.2.7 Orbital Debris2.2.8 Summary of Orbital Characteristics; 2.3 Satellite Constellations; 2.3.1 Considerations in Constellation Design; 2.3.2 Polar Constellations; 2.3.3 Inclined Orbit Constellations; 2.3.4 Hybrid Constellations; 2.3.5 Regional Coverage; 2.3.6 Constellations for Non-Real-Time Systems; 2.3.7 Use of Spot Beams; 2.3.8 Availability Considerations for Non-Geostationary Satellites; Revision; References; Chapter 3 Radio Link; 3.1 Introduction; 3.2 Spectrum Issues; 3.2.1 Spectrum Sharing Methods; 3.2.2 Spectrum Forecast Methodology; 3.3 Propagation Characteristics. 3.3.1 General Propagation Characteristics3.3.2 Land Mobile Channel; 3.3.3 Maritime Channel; 3.3.4 Aeronautical Channel; 3.3.5 System Implications; 3.4 Radio Link Analysis; Revision; References; Chapter 4 Modulation, Coding and Multiple Access; 4.1 Introduction; 4.2 Modulation; 4.2.1 MSS Requirements; 4.2.2 Preferences; 4.2.3 PSK Schemes; 4.2.4 Performance Comparison of Conventional Digital Modulation Schemes; 4.2.5 Coded Orthogonal Frequency Division Multiplexing (COFDM) Modulation Systems; 4.2.6 Spread Spectrum Modulation; 4.3 Coding; 4.3.1 Trellis-Coded Modulation (TCM). 4.3.2 Modulation and Coding Trends and Issues4.3.3 Automatic Repeat Request; 4.4 Multiple Access Schemes; 4.4.1 Comparison of Multiple Access Schemes; 4.4.2 Comparison of Spectral and Power Efficiency; Revision; References; Chapter 5 Fixed Earth Stations and User Terminals; 5.1 Introduction; 5.2 Gateways; 5.3 User Terminals; 5.3.1 Antennas; 5.3.2 Hand-Held UT; 5.3.3 Mobile Terminals; 5.4 Environmental Issues; 5.4.1 Biological Effects; Revision; References; Chapter 6 Spacecraft; 6.1 Introduction; 6.2 Satellites for MSS; 6.2.1 Transponders; 6.2.2 Antenna Systems. 6.2.3 Effect of Orbital Characteristics on Spacecraft Design.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Artificial satellites in telecommunication; Mobile communication systems; Artificial satellites in telecommunication; Mobile communication systems; TECHNOLOGY & ENGINEERING -- Mechanical; Artificial satellites in telecommunication; Mobile communication systems; Electronic books; Electronic books